Low Versus High Vacuum Suction Drainage of the Submuscular Pocket in Primary Breast Reconstruction: A Retrospective Study. Issue 4 (April 2018) - Pagliara, Domenico; Maxia, Sara; Faenza, Mario; Dessena, Lidia; Campus, GianVittorio; Rubino, Corrado
Abstract : Background: Placement of suction drainage in submuscular pockets is routinely performed in breast reconstruction. Days of drain permanence (DDP) are associated with hospital stay and related health care costs. The aims of this study are to retrospectively compare data related to DDP and total drainage volume between high and low vacuum suction drainage groups and to identify correlations with patient or surgery-related factors. Methods: We retrospectively analyzed data of 100 patients undergoing immediate or delayed breast reconstruction with expanders and implants. We considered 2 groups depending on suction pressure applied by 2 different surgical teams: group A (number, 50 patients) with high vacuum suction and group B (number, 50 patients) with low vacuum suction. Results: Days of drain permanence was not significantly different between group A and group B ( P = 0.451). The same was found for total drainage volume ( P = 0.183). The distribution of DDP was statistically different only between patients with or without intraoperative bleeding in group A ( P = 0.005) and smoking or nonsmoking patients in group A ( P = 0.045). Statistical significance was kept in multivariate regression. Conclusions: There is no significant difference in DDP and total drainage volume using low or high vacuum suction drainage in breast reconstruction. The only factors affecting drainage permanence were intraoperative filling of expander, smoking, and intraoperative bleeding. Therefore, we can reduce the DDP, avoiding overfilling of expander and using of high vacuum suction in nonsmoking patients and in patients with significant intraoperative bleeding.